Theoretical Modeling to Predict the Thermodynamic, Structural, Surface and Transport Properties of the Liquid Tl−Na Alloys at different Temperatures (Journal of Nepal Physical Society, 2017)
Theoretical modeling equations are developed by extending regular associated solution model to predict the thermodynamic and structural properties of the liquid Tl−Na alloys at higher temperatures. The thermodynamic properties have been predicted by computing activities of unassociated monomers (aTl and aNa) and free energy of mixing (GM) at temperatures 673 K, 773 K, 873 K and 973 K. The structural properties have been predicted by computing concentration fluctuation in long wavelength limit (SCC(0)), short range order parameter (α1) and ratio of mutual to intrinsic diffusion coefficients (DM/Did) at aforementioned temperatures. These properties have been then correlated with the modified Butler's model to predict the surface properties, such as surface concentrations of free monomers (XSTl and XSNa) and surface tension (σ) of the alloy at above mentioned temperatures.Journal of Nepal Physical SocietyVolume 4, Issue 1, February 2017, Page: 101-110